Influence of Salicylic Acid and Jasmonic Acid on Wheat Under Drought Stress. Issue 22 (16th December 2017) - Ilyas, Noshin; Gull, Robina; Mazhar, Roomina; Saeed, Maimona; Kanwal, Sidra; Shabir, Sumera; Bibi, Fatima
ABSTRACT: Salicylic acid and jasmonic acid play an important role in plants coping with abiotic stresses. An experiment was conducted to examine the effect of salicylic acid and jasmonic acid on wheat under drought. Seeds were primed with jasmonic acid (100µM) and salicylic acid (10 Mm). Water stress was applied by withholding water and each treatment was replicated three times with a factorial block design. Application of Salicylic acid and Jasmonic acid mitigated drought effects in wheat. Results revealed that 100µM Jasmonic acid was more effective than 10 mM SA. Drought decreased germination by 26%, whereas application of Jasmonic acid and Salicylic acid ameliorated stress with the increase of germination by 27% and 21%, respectively. An increase in the shoot length of 23% and 20% was observed with Jasmonic acid and Salicylic acid, under drought conditions. The increase in water potential was 60% and 47% with JA and SA while the increase in proline and soluble sugar was 14% and 25% respectively. The application of Jasmonic acid and Salicylic acid has a potential to enhance the growth of wheat plants under drought.